Protective effects of Nigella sativa on metabolic syndrome in menopausal women - Mohamad Ibrahim, Ramlah; Hamdan, Nurul Syima; Ismail, Maznah; Mohd Saini, Suraini; Abd Rashid, Saiful Nizam; Abd Latiff, Latiffah; Mahmud, Rozi (Tabriz University of Medical Sciences and Health Services, 2014)
PURPOSE: This study was conducted in menopausal women to determine the metabolic impact of Nigella sativa. METHODS: Thirty subjects who were menopausal women within the age limit of 45-60 were participated in this study and randomly allotted into two experimental groups. The treatment group was orally administered with N. sativa seeds powder in the form of capsules at a dose of 1g per day after breakfast for period of two months and compared to control group given placebo. Anthropometric and biochemical parameters were measured at baseline, 1st month, 2nd month and a month after treatment completed to determine their body weight, serum lipid profile and fasting blood glucose (FBG). RESULTS: The treatment group showed slight reduction with no significant difference in body weight changes of the respondents. However, significant (p<0.05) improvement was observed in total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), and blood glucose (p<0.05). CONCLUSION: These results suggested that treatment with N. sativa exert a protective effect by improving lipid profile and blood glucose which are in higher risk to be elevated during menopausal period.